A senolysis-based theragnostic prodrug strategy towards chronic renal failure. Issue 40 (26th September 2022) - Song, Yihe; Li, Xinming; Shi, Donglei; Sun, Tianyue; Liu, Wenwen; Li, Xiaokang; Qiao, Sicong; Chen, Xin; Guo, Yuan; Li, Jian
Abstract : Here, we report a senescence-associated β-galactosidase activatable theragnostic prodrug to pertinently treat chronic renal failure (CRF) in mice with the aid of fluorescence-guided senolysis, providing a creative molecular approach to CRF therapy. Abstract : Selective elimination of senescent cells (senolysis) has become a promising therapeutic strategy for the management of chronic renal failure (CRF), but the senolytic molecular pathways towards CRF therapy are limited. Here, we present for the first time a senescence-associated β-galactosidase (SA-β-gal) activatable theragnostic prodrug strategy to pertinently and effectively treat CRF in mice with the aid of fluorescence-guided senolysis. The signs of premature senescence, including the overexpression of β-gal, have been found in kidneys of mice with CRF, making this enzyme particularly suitable as a trigger of prodrugs for CRF therapy. With this unique design, our pioneering prodrug TSPD achieved the activation of a fluorophore for tracking and the specific release of the parent drug, gemcitabine, in β-gal-enriched cells after activation with SA-β-gal. In mice with CRF, abdominal administration of TSPD was effective for improvement of the kidney functions, supporting the feasibility of the SA-β-gal-dependent senolysis therapy towards CRF.